4. Q4c
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 2\sqrt{3} \times 5\sqrt{2} </code></p>
Similar Question 2
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 11\sqrt{2}(5\sqrt{3}) </code></p>
Similar Question 3
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 4\sqrt{3} \times 3\sqrt{6} </code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Simplify.</p><p><code class='latex inline'> \displaystyle -6\sqrt{2}(-\sqrt{11}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 8\sqrt{5}(\sqrt{10}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 11\sqrt{2}(5\sqrt{3}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle -4\sqrt{3} \times 8\sqrt{13} </code></p>
<p>Combine the following into a single radical. State the final answer in simplest mixed form of the radical.</p><p><code class='latex inline'>\displaystyle 3\sqrt{6} \times 6\sqrt{3}\times \sqrt{2} </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 3\sqrt{15}(-2\sqrt{3}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle -6\sqrt{2}(-\sqrt{11}) </code></p>
<p>Combine the following into a single radical. State the final answer in simplest mixed form of the radical.</p><p><code class='latex inline'>\displaystyle 4\sqrt{5}\times 3\sqrt{6} \times 7\sqrt{5} </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 5\sqrt{6}(2\sqrt{3}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 5\sqrt{3}(-\sqrt{5}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle \sqrt{5} \times \sqrt{7} </code></p>
<p>Combine the following into a single radical. State the final answer in simplest mixed form of the radical.</p><p><code class='latex inline'>\displaystyle \sqrt{6} \times 3\sqrt{5} </code></p>
<p>Write as a single power, then evaluate. Express answers in rational form.</p><p><code class='latex inline'> \displaystyle \frac{\sqrt{28}\sqrt{4}}{\sqrt{7}} </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 2\sqrt{3}(3\sqrt{2}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 3\sqrt{15}(-2\sqrt{3}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle \sqrt{11} \times \sqrt{6} </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 5\sqrt{6}(2\sqrt{3}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle -2\sqrt{6}(2\sqrt{6}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 11\sqrt{2}(5\sqrt{3}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle \sqrt{3}(5\sqrt{2}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle -2\sqrt{2}(4\sqrt{14}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle -7\sqrt{2} \times 5\sqrt{8} </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\displaystyle 5\sqrt{6}(2\sqrt{3}) </code></p>
<p>Combine the following into a single radical. State the final answer in simplest mixed form of the radical.</p><p><code class='latex inline'>\displaystyle 2\sqrt{3} \times 7\sqrt{7} </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 2\sqrt{3}(3\sqrt{2}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 2\sqrt{3} \times 5\sqrt{2} </code></p>
<p> Simplify the following to mixed form.</p><p><code class='latex inline'>\displaystyle 6\sqrt{32} \times 9\sqrt{3} </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle \sqrt{3}(5\sqrt{2}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle 4\sqrt{3} \times 3\sqrt{6} </code></p>
<p>Combine the following into a single radical. State the final answer in simplest mixed form of the radical.</p><p><code class='latex inline'>\displaystyle 3\sqrt{7} \times 2 \sqrt{3} \times 2\sqrt{7} </code></p>
<p>Write as a single power, then evaluate. Express answers in rational form.</p><p><code class='latex inline'> \displaystyle \sqrt{5}\sqrt{5} </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle \sqrt{5}(-\sqrt{7}) </code></p>
<p>Simplify.</p><p><code class='latex inline'> \displaystyle -6\sqrt{2}(-\sqrt{11}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle -2\sqrt{6}(2\sqrt{6}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle -2\sqrt{2}(4\sqrt{14}) </code></p>
<p>Expand and simplify</p><p><code class='latex inline'> \displaystyle 8\sqrt{5}(\sqrt{10}) </code></p>
How did you do?
Found an error or missing video? We'll update it within the hour! ðŸ‘‰
Save videos to My Cheatsheet for later, for easy studying.